The Swedish Economic Model - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2007)
The remarkable success of Sweden over the past 15 years has come after decades of sluggish growth, during which Sweden managed to lose its substantial lead in per-capita income. This substantiates the view that welfare cost and high taxes reduce growth and endanger competitiveness. Since then, however, Sweden has engaged in a remarkable strategy of reforming the budget process, increasing the flexibility of its labour market and boosting investment in the future. Incentives have been changed to achieve greater flexibility and to adapt to changes resulting from globalisation.
Keywords: 330; Welfare models; corporatism; economic performance; competitiveness; Sozialstaat; Korporatismus; Standortfaktor; Wirtschaftswachstum; Wirtschaftsordnung; Schweden